Hepatoprotective effect of DL-methionine on diclofenac-induced hepatotoxicity in albino rats: an experimental study - Dass, Ervilla; Sattigeri, Bhagya Manoj (International Journal of Research in Medical Sciences, 2018)
Background: Liver is the main detoxifying organ, which is affected by most of the drugs and xenobiotic agents that could result in liver damage. The present study was designed to evaluate the hepatoprotective effect of DL-Methionine against experimentally induced liver injury in albino rats. Methods: Hepatotoxicity was induced by administering high doses of positive control drug Diclofenac sodium in albino rats, which was confirmed by estimating Liver Function Tests. Hepatoprotective effect was determined by administering DL- Methionine concomitantly with positive control drug. Albino rats were administered with DL-Methionine (700 mg/kg and 1400 mg/kg) respectively as a single oral dose, concomitantly with positive control drug Diclofenac sodium (96 mg/kg and 240 mg/kg) respectively. After 24-hours of post-treatment, serum levels of the liver enzymes were evaluated to demonstrate the hepatoprotective effect of DL-Methionine on drug-induced hepatotoxicity, and all the liver samples were examined for the histopathological study. Results: Significant increase in serum transaminase enzymes were observed by the positive control drug Diclofenac sodium. There was significant reduction in the serum transaminases on concomitant administration of DL-Methionine with Diclofenac sodium. Liver injury induced by positive control drug; and its protection with DL-Methionine was revealed by histopathological study. The combination of Diclofenac sodium and DL-Methionine showed no significant histopathological difference when compared to the normal liver section. Conclusions: The results reveal that, DL-Methionine significantly prevented the rise in transaminases levels produced by hepatotoxic doses of the positive control drug.